2020
DOI: 10.3390/pathophysiology27010002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Five International HBV Treatment Guidelines: Recommendation for Resource-Limited Developing Countries Based on the National Study in Nepal

Abstract: Hepatitis B virus (HBV) infects the liver, causing cirrhosis and cancer. In developed countries, five international guidelines have been used to make a decision for the management of patients with chronic HBV infection. In this review, since the guidelines were established by clinical and epidemiological data of developed countries, we aimed to evaluate whether (1) HBV patient profiles of developing countries are similar to developed countries, and (2) which guideline can be applicable to resource-limited deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently, Remi Collin found that hepato-renal index using conventional US was superior to continuous CAP using FibroScan (Echosens, Paris, France) in diagnosing hepatic steatosis (AUROC 0.91 vs. 0.79) [30]. Although CAP has been extensively validated to have excellent diagnostic performance for detecting hepatic steatosis, this new technology is not as widely available as traditional ultrasonography, which makes it less appealing, especially in undeveloped regions [31]. Thus, conventional B-mode ultrasonography is still the first choice of screening tool for MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Remi Collin found that hepato-renal index using conventional US was superior to continuous CAP using FibroScan (Echosens, Paris, France) in diagnosing hepatic steatosis (AUROC 0.91 vs. 0.79) [30]. Although CAP has been extensively validated to have excellent diagnostic performance for detecting hepatic steatosis, this new technology is not as widely available as traditional ultrasonography, which makes it less appealing, especially in undeveloped regions [31]. Thus, conventional B-mode ultrasonography is still the first choice of screening tool for MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, for many elastography devices using 2D-SWE in patients with NAFLD, valid data for determining fibrosis with histology as the reference standard are missing. Furthermore, in resource-limited developing countries, the availability of elastography-capable sonography devices is limited [ 49 ].…”
Section: Liver Fibrosismentioning
confidence: 99%